Kinerja Petugas Lapangan Seksi Kebersihan Dinas Perumahan dan Kawasan Pemukiman Kota Prabumulih - Erlangga, Yudha; Putra, Raniasa; Hendrasmo, Ignasius (Journal of Law & Policy Review, 2023)
Villages play an important role in National Development. The Village Government is obliged to convey public information to the community. This study examines Village Funds in Mekar Sari Village, Kecematan Rawas Ilir, and North Musi Rawas Regency, which have received Village Funds. The research method used is qualitative descriptive to explain the effectiveness of the use of Village Funds in Mekar Sari Village. The results of the study show that the village head has improved the standard of living of the community by opening jobs, such as taking stones and sand, and increasing the original income of the village. Village income has increased since the existence of the Village Fund. However, there were shortcomings in the village head's understanding of the effectiveness of the use of Village Funds by the Work Plan Program in the North Musi Rawas Regent Regulation No. 4 of 2017 and the lack of openness between the village government and the community to improve the standard of living and quality of life of the community.